Validation of lesion durability following pulmonary vein isolation using the new third-generation laser balloon catheter in patients with recurrent atrial fibrillation. Issue 5 (November 2021) - Tohoku, Shota; Bordignon, Stefano; Chen, Shaojie; Bologna, Fabrizio; Urbanek, Lukas; Operhalski, Felix; Chun, KR Julian; Schmidt, Boris
Highlights: This study revealed the data following pulmonary vein isolation with the successor laser balloon catheters. The continuous robotic motor driven ablation led to higher index lesion durability. Right superior pulmonary vein was the most common reconnected vein irrespective of generations. The need for focal energy reduction was a predictor of pulmonary vein reconnection. Abstract: Background: The second- and third-generation endoscopic ablation systems (EAS2 and EAS3) have been launched in recent years. We aimed to assess the lesion durability as well as gap localization using the multigenerational novel technologies in patients with recurrent atrial fibrillation (AF). Methods: Consecutive patients who underwent second ablation for recurrent AF following the initial pulmonary vein isolation (PVI) with EAS2 or EAS3 were retrospectively investigated. The persistent durability of PVI, gap localization at the second procedure, and procedural/anatomical features of durable PVI were analyzed. Results: Among 225 patients treated with EAS3 ( N = 125) and EAS2 ( N = 100), 34 patients (EAS3: 13 patients, 50 PVs, EAS2: 21 patients, 82 PVs) underwent a second procedure because of recurrent AF mean 11.9 ± 9.3 months after the initial procedure. Persistent isolation of all four PVs was recorded in 6 (46.2%) patients in EAS3 group and 4 (19.1%) patients in EAS2 group ( p = 0.130). Ninety-one out of 132 (68.9%) PVs were persistently isolated with a higher rate in EAS3 group (82.0% vs. EAS2 group: 61.0%, p = 0.0113). A total of 45 gaps were recorded in 41 PVs. Right superior PV (RSPV) was the predominantly common reconnected vein (15 gaps, 14 PVs) irrespective of generations (EAS3: 4 gaps in 3 PVs and EAS2: 12 gaps in 11 PVs). Logistic multivariate regression analysis revealed ablation without reduced energy dose (5.5–7 W) as an independent predictor of durable PVI [adjusted OR: 3.70, 95% CI (1.408–10.003)], p = 0.008]. Conclusion: The technical innovation resulted in a higher lesion durability in EAS3-guided PVI in patients with recurrent AF. The most common gap location was found at RSPV in successor EASs. Ablation without reduced energy was a predictor of durable PVI in successor EASs. Graphical abstract: Image, graphical abstract